(untitled)
Five modern catalysts have been synthesized with various ligand structures for polymerization of aqueous polar and non-polar olefins. New complexes of titanium [TiLCl2] Catalyst [TiLCl2] LH2=2-(3,5-Di-tert-butyl-2-hydroxybenzylamino-hydroxybenzylamino)-succinic acid] [Catalyst 1]